The Role of the Everything But Arms Trade Preferences Regime in the EU Development Strategy - Katerina Gradeva; Inmaculada Martínez-Zarzoso (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2010)
This study examines the effect of the Everything But Arms (EBA) trade preferences regime on exports from African, Caribbean and Pacific (ACP) Least Developed Countries (LDCs) to the European Union (EU). With this aim, an augmented gravity model is estimated for exports from the 79 ACP countries to the EU-15 for the time period 1995 to 2005 using panel data techniques. The model estimates are used to quantify the effect of the EBA preferences on the ACP LDCs' export performance and to compare it with the impact of official development assistance. In addition to their separate effects, the combined impact of EBA and aid flows is estimated. The main results show a negative effect of the EBA regime on exports. Otherwise, the combined effect of the EBA and aid on exports is positive, supporting an EU development strategy that includes both sorts of assistance, aid and trade preferences.
Keywords: O24; C23; F13; F35; 330; development aid; trade preferences; Everything But Arms; panel data